J05 Interim results from cohort 1 of the double-blind, dose-escalation phase I/II clinical trial of amt-130 (HD-genetrx-1) for early-stage huntington's disease (HD). (12th September 2022) - Furr Stimming, Erin; Sung, Victor; Testa, Claudia; Kostyk, Sandra; Ross, Christopher A; Samii, Ali; Geschwind, Michael D; Hall, Deborah; Dayalu, Praveen; Lonser, Russell; Elder, Brad; Larson, Paul S; et al.
Abstract : Background: Huntingtin (HTT) lowering therapies hold great promise to slow or halt neurodegeneration in Huntington's disease (HD). AMT-130 is an investigational AAV5-based gene therapy that expresses an engineered microRNA to specifically bind to huntingtin exon 1, thereby lowering total HTT mRNA. Aims: We initiated a double-blinded first-in-human study to investigate AMT-130 in early-stage patients and here describe interim 12-month results from the low-dose cohort (NCT04120493 ). Methods: Inclusion criteria were DCL 3-4, TFC 9-13, ≥40 CAG repeats, and caudate/putamen volumes greater than a prespecified minimum. Participants received one-time AMT-130 administration using MRI-guided, convection-enhanced stereotactic neurosurgical delivery directly into six sites bilaterally (3/side) in the striatum, or a sham surgical procedure. Results: At baseline, ages of 10 enrolled participants in Cohort 1 ranged from 34-58 years (mean:49), historical CAG repeats from 41-44 (mean:42), CAP scores from 318-542 (mean:426), TFC from 10-13 (mean:11.9) and TMS from 7-23 (mean:13.3). At 12-months post-treatment, the most common treatment-emergent adverse event was transient post-procedural headache (70%). Two serious adverse events judged to likely be unrelated to AMT-130 were observed: an upper extremity DVT at an intravenous line site presenting 1-week post-procedure, and brief post-operative delirium; both resolved. At 12-months post-treatment, CSF NfL returned to near baseline levels following an initial increase and the mean CSF mHTT decreased 53.8% (range:44-71%) compared to baseline. Conclusions: Follow up of participants is ongoing. Cohort 1 interim data thus far supports the safety and tolerability of a one-time infusion of AMT-130 in patients with early-stage HD.